2010
DOI: 10.1152/ajpheart.00656.2010
|View full text |Cite
|
Sign up to set email alerts
|

Transforming growth factor-β1regulation of C-type natriuretic peptide expression in human vascular smooth muscle cells: dependence on TSC22D1

Abstract: C-type natriuretic peptide (CNP) possesses nitric oxide-like signaling mechanisms and actions in the vasculature, including the inhibition of fibrosis and vascular remodeling through counterregulation of transforming growth factor-β (TGF-β) signaling. The leucine zipper protein transforming growth factor stimulated clone 22 domain 1 (TSC22D1), cloned via its presumed binding to a GC-rich element in the CNP promoter, was the first protein to be described as a CNP transcription factor, but the lack of supporting… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
12
0

Year Published

2011
2011
2018
2018

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 16 publications
(13 citation statements)
references
References 29 publications
(36 reference statements)
1
12
0
Order By: Relevance
“…The process by which GH stimulates CNP secretion was not addressed in this study, but the failure of short-term GH to affect plasma NTproCNP (or skeletal growth) in rapidly growing healthy lambs despite the large increases in plasma IGF1 suggests that neither GH nor IGF1 directly stimulates CNP gene expression. A range of genes or transcription factors including transforming growth factor b, fibroblast growth factor, PDGF bb, TSC 22 (Suga et al 1992, Mendonca et al 2010) and KLF2 (Parmar et al 2006) are reported to increase CNP mRNA in vascular endothelial cells, but little is known of the mechanisms regulating CNP gene expression within the growth plate. Presumably downstream effectors of GH and IGF1, and possibly GH-induced mechanosensitive pathways (Zhang et al 2011), for example, by stimulating KLF2 (Cameron et al 2009), are involved.…”
Section: Discussionmentioning
confidence: 99%
“…The process by which GH stimulates CNP secretion was not addressed in this study, but the failure of short-term GH to affect plasma NTproCNP (or skeletal growth) in rapidly growing healthy lambs despite the large increases in plasma IGF1 suggests that neither GH nor IGF1 directly stimulates CNP gene expression. A range of genes or transcription factors including transforming growth factor b, fibroblast growth factor, PDGF bb, TSC 22 (Suga et al 1992, Mendonca et al 2010) and KLF2 (Parmar et al 2006) are reported to increase CNP mRNA in vascular endothelial cells, but little is known of the mechanisms regulating CNP gene expression within the growth plate. Presumably downstream effectors of GH and IGF1, and possibly GH-induced mechanosensitive pathways (Zhang et al 2011), for example, by stimulating KLF2 (Cameron et al 2009), are involved.…”
Section: Discussionmentioning
confidence: 99%
“…Therefore its proposed role as a direct enhancer of CNP transcription has remained in question. Recent studies in our laboratory using siRNA gene silencing techniques have shown that TSC22D1-silencing significantly reduces both PDGF-up-regulated CNP transcript in human aortic SMC and TGF-␤-up-regulated transcript in coronary artery-derived SMC [52]. These results suggest that in human vascular smooth muscle cells, TSC22D1 expression and activity could represent a critical element in a final common pathway leading to increased CNP expression induced by different stimuli.…”
Section: Putative Transcription Factorsmentioning
confidence: 73%
“…Recent studies [31,99] suggest that these protein variants could perform unrelated, or even antagonistic functions in the mammalian cell; e.g., although the short form of TSC22D1 has been described many times as a tumor suppressor, the long form in contrast promotes proliferation, growth and cell survival [99]. Interestingly, in our recent studies of the effects of TSC22D1 silencing on CNP expression in vascular smooth muscle cells, [52], we could only identify a long form of the protein (∼120 kD) in Western blots, yet the downregulation of this protein with TSC22D1 siRNA resulted in reduced production of CNP transcript in these cells.…”
Section: Putative Transcription Factorsmentioning
confidence: 90%
See 2 more Smart Citations